PENGEMBANGAN SISTEM DIAGNOSA HAMA DAN PENYAKIT PADA TANAMAN JAGUNG BERDASARKAN INTENSITAS KERUSAKAN MENGGUNAKAN METODE CERTAINTY FACTOR - Kusumahdinata, R. Ramdan; Sudiarjo, Aso; Hikmatyar, Missi; Ramadhan, R. Arif Malik (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
Corn plants have the potential to be attacked by pests or diseases that can appear at any time such as leaf blight, leaf rust and downy mildew. Obstacles facing farmers are sometimes the lack of information about the symptoms found so that sometimes the diagnosis is not correct and the treatment is wrong, resulting in reduced corn production. Along with technological advances, a technology has also been produced that can adopt the process of human thinking, namely artificial intelligence technology or AI or Artificial Intelligence. including an expert system, which is a computer-based system that adopts the knowledge and experience of an expert, and reasoning techniques to solve a problem, similar to how an expert in a particular field solves the problem. The development that will be made is "Development of a Diagnostic System for Pests and Diseases in Corn Plants Based on Damage Intensity Using the Certainty Factor Method".